2021
DOI: 10.1177/2333794x211045822
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eight or More Antenatal Care Contacts: Findings From Multi-Country Nationally Representative Data

Abstract: Optimal antenatal care is an important service required by women and babies. To promote healthy motherhood and for positive pregnancy outcomes, World Health Organization recently recommended a minimum of 8 ANC contacts. We aim to explore the prevalence of 8 or more ANC contacts using multi-country data. Urban dwellers, mothers with secondary or higher education, women from high household wealth, early birth order, and older mothers at childbirth had higher prevalence of 8 or more ANC contacts respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
(71 reference statements)
3
15
2
Order By: Relevance
“…Secondly, the existence of structural challenges such as poor roads and transportation networks to health facilities could explain the poor utilization of the eight or more contacts [31]. Our findings are similar to those reported by a study that used Nigeria DHS data at 20.3% [32], but higher than what was reported in Benin (8%) [33], the pooled prevalence of 7.7% from DHS data of eight countries in SSA (Guinea 3.3%, Mali 3.5%, The Gambia 4.3%) [32], 6.8% from 36 SSA countries [34], and 13.0% DHS data of Asian and SSA countries [35]. As much as this shows that Sierra Leone has one of the highest proportions of utilization of eight or more ANC contacts compared to other countries in SSA, is still below the level recommended by WHO [15].…”
Section: Discussionsupporting
confidence: 90%
“…Secondly, the existence of structural challenges such as poor roads and transportation networks to health facilities could explain the poor utilization of the eight or more contacts [31]. Our findings are similar to those reported by a study that used Nigeria DHS data at 20.3% [32], but higher than what was reported in Benin (8%) [33], the pooled prevalence of 7.7% from DHS data of eight countries in SSA (Guinea 3.3%, Mali 3.5%, The Gambia 4.3%) [32], 6.8% from 36 SSA countries [34], and 13.0% DHS data of Asian and SSA countries [35]. As much as this shows that Sierra Leone has one of the highest proportions of utilization of eight or more ANC contacts compared to other countries in SSA, is still below the level recommended by WHO [15].…”
Section: Discussionsupporting
confidence: 90%
“…This could have led to an underestimation of the prevalence of ANC8+, as it was not recommended before 2016. The prevalence of ANC8+ in our study was also higher than the overall prevalence of ANC8+ across 15 LMICs reported in a recent study [ 27 ]. The low compliance with ANC8+ across many of the countries in our study could have been due to several reasons.…”
Section: Discussioncontrasting
confidence: 80%
“…One study reported that the average number of antenatal care visits for women in Vietnam was 7.7 visits in urban areas and 4.4 visits in rural areas [42]. The WHO recently recommended a minimum of eight antenatal visits [43]. We did not report the number of antenatal care visits in our study as this information was not retrospectively available.…”
Section: Discussionmentioning
confidence: 93%